The critical point of Bootstrap and Lattice QCD - Antoniou, N. G.; Diakonos, F. K.; Kapoyannis, A. S. (HNPS Advances in Nuclear Physics, 2020)
It is shown that the hadronic matter formed at high temperatures, according to the prescription of the statistical bootstrap principle, develops a critical point at nonzero baryon chemical potential. The location of the critical point is evaluated with the use of lattice QCD pressure.